UPGRADING AND REPAIRING PCS - MUELLER SCOTT (NOIDA PEARSON EDUCATION INC, 2016)
"Upgrading and Repairing PCs" by Scott Mueller is widely regarded as the definitive, encyclopedic "bible" for computer technicians, IT professionals, and serious PC enthusiasts. For decades and across more than 20 editions, this book has been the industry's go-to reference for in-depth, technically exhaustive information on every component of a personal computer. It goes far beyond simple step-by-step guides, providing deep-dive explanations of how components like motherboards, processors, memory, and storage systems actually work, including details on bus architectures, chipsets, and low-level specifications. The book is a masterclass in comprehensive hardware knowledge, prized for its meticulous accuracy and its focus on diagnostics, enabling professionals to truly understand, troubleshoot, and repair PC hardware at a fundamental level.
COMPUTER UPGRADE & REPAIR
COMPUTERS
Keywords: COMPUTERS